2021
DOI: 10.1149/1945-7111/abdeea
|View full text |Cite|
|
Sign up to set email alerts
|

Multiple Reaction Pathways for the Oxygen Evolution Reaction May Contribute to IrO2 (110)’s High Activity

Abstract: Density functional theory calculations in conjunction with statistical mechanical arguments are performed on the rutile IrO 2 (110) facet in order to characterize multiple reaction pathways on the surface at the highest active limit (the stoichiometric surface with all metal sites available) and at the lowest active limit (the oxygen-terminated surface). Alternative pathways to the oxygen evolution reaction (OER) are found, with multiple pathways determined at each step of the four proton-coupled electron tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…The anodic reaction of water oxidation transpired by adsorption of OH – and O adsorption species (O abs ) on the surface of the Cu­(OH) 2 NWs@NiCo-LDH electrode (designated M). The reaction occurred via two pathways as …”
Section: Resultsmentioning
confidence: 99%
“…The anodic reaction of water oxidation transpired by adsorption of OH – and O adsorption species (O abs ) on the surface of the Cu­(OH) 2 NWs@NiCo-LDH electrode (designated M). The reaction occurred via two pathways as …”
Section: Resultsmentioning
confidence: 99%
“…Kohn–Sham density functional theory (DFT) is the most commonly employed electronic structure method and has been highly successful at identifying reaction sites, structures, and reaction mechanisms in catalysis. Briefly, DFT solves the Schrödinger equation for independent single electrons in an effective potential that approximately captures electron–electron interactions based on the electron density. Energy contributions beyond the average Coulomb interaction of electrons are captured by the exchange-correlation functional, which is typically treated semilocally as a function of only the local electron density and its gradients (see ref for a detailed introduction).…”
Section: Electronic Structure Accuracymentioning
confidence: 99%
“…The electronic structure of Ru atoms can be altered by doping with heteroatoms. The OER activity of the catalyst may be significantly enhanced by speeding the dissociation of water and lowering the reaction intermediate adsorption and reaction energy barriers [ 73 ]. Prior research has shown that the inclusion of transition metal atoms, such as Co and Ni, into the Ru lattice to construct multi-alloys can enhance the charge distribution and surface structure of the catalyst, hence improving its catalytic activity.…”
Section: Progress In Catalysts For the Oermentioning
confidence: 99%